Hydrogen Bonding in Aprotic Solvents, a New Strategy for Gelation of Bioinspired Catecholic Copolymers with N‐Isopropylamide. Issue 5 (16th January 2015) - Vatankhah‐Varnoosfaderani, Mohammad; GhavamiNejad, Amin; Hashmi, Saud; Stadler, Florian J.
<x xml:space="preserve">Abstract</x> Copolymers of N‐isopropylacrylamide (NIPAM) and dopamine methacrylate can establish a reversible, self‐healing 3D network in aprotic solvents based on hydrogen bonding. The reactivity and hydrogen bonding formation of catechol groups in copolymer chains are studied by UV–vis and 1H NMR spectroscopy, while reversibility from sol to gel and inverse as well as self‐healing properties are tested rheologically. The produced reversible organogel can self‐encapsulate physically interacting or chemically bonded solutes such as drugs due to thermosensitivity of the used copolymer. This system offers dual‐targeted and controlled drug delivery and release—by slowing down release kinetics by supramolecular bonding of the drug and by reducing diffusion rates due to modulus increase. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>